Optimal Contracts under Costly State Falsification - Lacker, Jeffrey M.; Weinberg, John A. (Journal of Political Economy, 1989)
We examine an exchange economy with two agents: one risk neutral with a certain endowment and a second risk averse with a random endowment. The realization of the endowment is public but can be falsified by the second agent at a cost. For a broad class of falsification cost functions the optimal no-falsification contract is noncontingent on a left-hand interval and strictly increasing with a slope strictly less than one on a right-hand interval. Under a mild further restriction, optimal no-falsification contracts are, in addition, piece-wise linear. Optimal contracts may in general require falsifying the state, but for a set of the highest endowment realizations there is no falsification. We find simple conditions under which the optimal contract is a no-falsification contract. The model has applications that include financial, insurance, and employment contracts and tax policy.